2021
DOI: 10.1186/s12902-021-00753-2
|View full text |Cite
|
Sign up to set email alerts
|

Significant abnormal glycemic variability increased the risk for arrhythmias in elderly type 2 diabetic patients

Abstract: Background Little is known about whether the influence of glycemic variability on arrhythmia is related to age in type 2 diabetes mellitus (T2DM). Therefore, we aimed to compare the association between glycemic variability and arrhythmia in middle-aged and elderly T2DM patients. Methods A total of 107 patients were divided into two groups: elderly diabetes mellitus group (EDM, n = 73) and middle-aged diabetes mellitus group (MDM, n = 34). The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In accordance with this, glycaemic control in the form of daily insulin injections has been shown to shorten QTc in patients with T2DM. 162 Increased QTc has also been reported in patients with type 1 diabetes 163,164 , and glycaemic variability alone has been shown to increase the incidence of cardiac arrhythmia in individuals with T2DM, 165 further supporting that long-term hyperglycaemia may affect cardiac electrophysiology as well.…”
Section: Qt Intervalmentioning
confidence: 88%
“…In accordance with this, glycaemic control in the form of daily insulin injections has been shown to shorten QTc in patients with T2DM. 162 Increased QTc has also been reported in patients with type 1 diabetes 163,164 , and glycaemic variability alone has been shown to increase the incidence of cardiac arrhythmia in individuals with T2DM, 165 further supporting that long-term hyperglycaemia may affect cardiac electrophysiology as well.…”
Section: Qt Intervalmentioning
confidence: 88%
“…40 On the other hand, clinical studies have shown that a high GV is associated with prolonged QTc duration and QTc dispersion, 41 as well as an elevated risk of arrhythmia in individuals with diabetes. 42,43 This implies that a high fluctuation in glucose levels may also pose a risk of arrhythmia in patients with HF. In fact, a preliminary investigation indicated that a significant 24-h fluctuation in blood glucose levels was linked to an increase in ventricular ectopic activity in patients with HF and concomitant diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent investigation indicated that variations in glucose levels may induce apoptosis in cardiomyocytes by activating the signalling pathway of endoplasmic reticulum stress in rats with diabetes and in primary cardiomyocytes 40 . On the other hand, clinical studies have shown that a high GV is associated with prolonged QTc duration and QTc dispersion, 41 as well as an elevated risk of arrhythmia in individuals with diabetes 42,43 . This implies that a high fluctuation in glucose levels may also pose a risk of arrhythmia in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated that diabetic patients have more ECG abnormalities and a higher incidence of ventricular arrhythmias compared with normal individuals. [23][24][25] Recent studies have demonstrated that GF are more harmful to patients with DM than sustained hyperglycemia. However, the relationship between GF and lethal ventricular arrhythmias, such as VT or VF, remains elusive.…”
Section: Discussionmentioning
confidence: 99%